1987
DOI: 10.1002/ecjb.4420701206
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the transient wafer temperature distribution in a furnace for semiconductor fabrication processes

Abstract: In the high‐temperature process of semiconductors, the temperature distribution on the wafer surface during the procedures of the wafer insertion into and removal from the oxidation or diffusion furnace is important in determining the density of the dislocation due to the thermal stress and the uniformities of both the oxide thickness and the diffusion depth. As the size of a wafer and the density of integration increase, the analysis of the thermal transient characteristics becomes more important. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Mokuya et al investigated the temperature distributions in regularly spaced wafers in a row in a furnace tube theoretically and experimentally, and showed that the temperature gradient in a wafer becomes larger from the bottom position (Y ϭ 0) to the top position and the distribution was different according to the wafer set position on the boat. [34][35][36] This indicates that the thermal stress which is nearly proportional to the temperature gradient 37 becomes higher near the top position of wafer, i.e., near the orientation flat in the present work. The stress induced in the Si substrate enhances the generation of point defects (interstitial and vacancy).…”
Section: Resultsmentioning
confidence: 53%
“…Mokuya et al investigated the temperature distributions in regularly spaced wafers in a row in a furnace tube theoretically and experimentally, and showed that the temperature gradient in a wafer becomes larger from the bottom position (Y ϭ 0) to the top position and the distribution was different according to the wafer set position on the boat. [34][35][36] This indicates that the thermal stress which is nearly proportional to the temperature gradient 37 becomes higher near the top position of wafer, i.e., near the orientation flat in the present work. The stress induced in the Si substrate enhances the generation of point defects (interstitial and vacancy).…”
Section: Resultsmentioning
confidence: 53%